The Effect of Price Perception, the Physical Evidence Dimension, and the Responsiveness Dimension on Customer Satisfaction at Ah Pek Kopitiam in Depok - Titiek Irewati (CV. Publikasi Indonesia, 2026)
The rapid growth of the culinary industry in Indonesia, particularly the increasing popularity of Kopitiam establishments, has intensified competition. To succeed, businesses like Ah Pek Kopitiam must understand the key drivers of customer satisfaction. Objective: This study aims to analyze the effect of price perception, the physical evidence dimension, and the responsiveness dimension on customer satisfaction at Ah Pek Kopitiam, Depok. Methods: This research employs a quantitative approach with a causal design. A sample of 100 respondents was selected using a convenience sampling technique. Data were collected through a structured questionnaire using a Likert scale and analyzed using multiple linear regression. Findings: The results show that price perception (X1), physical evidence (X2), and responsiveness (X3) each have a partial and significant positive effect on customer satisfaction. The regression model is Y = 6.439 + 0.221X1 + 0.225X2 + 0.233X3. Simultaneously, these three variables have a significant effect on customer satisfaction, with an R² value of 0.452. This indicates that 45.2% of customer satisfaction can be explained by these three variables, while the remaining 54.8% is influenced by other factors not examined in this study. Conclusion and Implication: This study confirms that price perception, physical evidence, and responsiveness are important determinants of customer satisfaction at Ah Pek Kopitiam. To enhance customer satisfaction, the management should focus on improving the speed of service, optimizing competitive pricing, and maintaining the quality of the physical environment, as these aspects are highly valued by customers. Keywords: Price Perception, Physical Evidence, Responsiveness, Customer Satisfaction, Kopitiam.